Relationship amongst mood, propensity to forgive, and mental-health problems in female Italian adolescents. Issue 8 (14th September 2017) - Cabras, Cristina; Loi, Giorgia; Sechi, Cristina; Mondo, Marina
ABSTRACT: Adolescence is a time of rapid physical, neurological, and cognitive transformations, as well as shifts in relationships through the development of new roles across social domains. As an outcome of such transformations, adolescents may become vulnerable to mental-health problems during this period. Therefore, it is important to focus on predictors of mental-health problems to identify effective prevention strategies. This study examined the mediating role of propensity to forgive in the relationship amongst mood and mental health in a sample of female Italian students who consisted of 342 nonreferred adolescents. Participants completed the Positive Affect-Negative Affect Schedule-Short Form, the Heartland Forgiveness Scale, and the General Health Questionnaire. The mediation analysis results suggest that mood has a direct effect on mental-health problems and an indirect effect through propensity to forgive. The results suggest the importance of considering implementing education programmes and forgiveness interventions within clinical practice as a means of reducing mental-health problems.